Analysis of Occupational Health and Safety Management of Hospital Employees During a Pandemic: A Case Study of Covid-19 in Employees at Kendal Islamic Hospital - Joko Sudiarto; Chriswardani Suryawati; Hanifa Maher Denny (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: In 2019, in December to be precise, an acute respiratory disease caused by the corona virus/ COVID-19 (corona virus deiase-19) was discovered. The transmission of COVID-19 to health workers is a very important issue in this pandemic era. In Indonesia, data from the COVID-19 report on July 15 2021, the number of deaths recorded by health workers was 1,292 due to COVID-19. The data found that the spread of COVID-19 has also infected employees at the Kendal Islamic Hospital. Total population of 512 employees, 20% exposed to COVID-19, namely 118 employees, with the highest distribution of cases occurring in medical personnel, namely 14%. Objective: Occupational health and safety is an effort and effort to create protection and security from the risk of accidents and hazards, both physical, mental and emotional for workers. Methods: This research is a qualitative research with a single case study design. Data collection using purposive sampling technique was carried out by observation and in-depth interviews. This research data collection was carried out by observing the management of the health and safety of hospital employees during the Pandemic: Case studies of COVID-19 among employees at Kendal Islamic Hospital. Secondary data is used to support and relate to research variables or research problems. Results: The management of COVID-19 at RSI Kendal has basically adapted to regulations set by the government starting from policies/regulations, provision of physical facilities, medical devices, medicines and BMHP as well as in the provision of PPE. However, there are still several obstacles in its implementation, so that many employees are still infected and exposed to COVID-19. This is influenced by many factors, including fatigue, decreased immunity, stress and there are still many officers and employees who are not disciplined with the health program. Conclusion: In general, the management of employee health and safety at Kendal Islamic Hospital during the pandemic has been carried out in accordance with the government's standards for handling COVID-19.